Empowered or Not: English Teachers’ Lived Experiences in Teaching Struggling High School Readers - Gecana, Romjohn Philip; Shienna Marie Caparas (International Journal on Integrated Education, 2025)
Reading is a fundamental skill vital to academic success, cognitive development, and lifelong learning. Despite its significance, a substantial number of high school students continue to face challenges in reading fluency, vocabulary, and comprehension. The World Bank's 2022 data on learning poverty revealed that approximately 90% of Filipino children aged 10 cannot read or understand a simple text. Recognizing the critical role teachers play in literacy development, this study emphasized the need to amplify their voices in creating more effective interventions and support systems for teachers and struggling readers. This qualitative phenomenological research explored the lived experiences of English teachers in teaching struggling high school readers at Balibago Integrated High School in the Division of Santa Rosa. Data were collected through semi-structured interviews with purposefully selected nine participants and analyzed using Colaizzi's seven-step method. The study revealed ten (10) superordinate themes and forty-three (43) subordinate themes describing the challenges faced by English teachers when teaching struggling readers, their pedagogical strategies and approaches, professional growth, and career advancement opportunities in managing the demands and challenges in teaching struggling high school readers, and practical recommendations for teachers handling struggling readers. The study concluded that English teachers faced several challenges in teaching struggling high school readers, including internal and external impediments to reading development. Teachers also employ various strategies to address reading difficulties and engage struggling readers. Moreover, teachers identified professional development opportunities and their advantages in teaching struggling readers.